2014
DOI: 10.1016/j.jcin.2014.08.002
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Follow-Up of the Melody Transcatheter Pulmonary Valve Multicenter Post-Approval Study

Abstract: This first prospective, real-world experience with the Melody TPV in the United States demonstrates continued high procedural success, excellent short-term TPV function, and low reintervention and reoperation rates at 1 year. (Melody Transcatheter Pulmonary Valve Post-Approval Study; NCT01186692).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
100
1
6

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(113 citation statements)
references
References 19 publications
5
100
1
6
Order By: Relevance
“…However, in the 113 patients who were alive and free from reintervention a median of 4.5 years after TPVR, Melody valve function was unchanged from the early postimplantation echocardiogram. Short-term follow-up from prior studies reported similarly excellent valve function, 2,3,[5][6][7]9 but no data on longer-term valve function have been published. In that regard, the findings of this study are encouraging.…”
Section: Intermediate-term Melody Valve Function and Clinical Outcomementioning
confidence: 95%
See 1 more Smart Citation
“…However, in the 113 patients who were alive and free from reintervention a median of 4.5 years after TPVR, Melody valve function was unchanged from the early postimplantation echocardiogram. Short-term follow-up from prior studies reported similarly excellent valve function, 2,3,[5][6][7]9 but no data on longer-term valve function have been published. In that regard, the findings of this study are encouraging.…”
Section: Intermediate-term Melody Valve Function and Clinical Outcomementioning
confidence: 95%
“…[2][3][4] A number of single-center and multicenter reports have confirmed that TPVR is technically reproducible and results in excellent early and short-term outcomes, with reduction of right ventricular outflow tract (RVOT) obstruction, elimination of pulmonary regurgitation (PR), and clinical improvement. [2][3][4][5][6][7][8][9] At a functional level, TPVR is followed by improved circulatory efficiency and ventricular strain, enhanced cardiopulmonary exercise function in some patients, and better quality of life. [10][11][12][13][14][15][16][17][18] Although these and other reports helped substantiate TPVR as a valuable tool in the management of patients with postoperative RVOT dysfunction, the lack of longer-term follow-up data remains an important limitation in the Melody valve literature.…”
mentioning
confidence: 99%
“…The patients are teenagers or young adults, often after several previous surgical interventions. TPVR has become an alternative method of treatment for those with residual stenosis or regurgitation [2,10,[13][14][15]. Critically, this treatment is also possible for patients after TOF patch surgery, a large group of patients with congenital heart diseases.…”
Section: Discussionmentioning
confidence: 99%
“…All procedures were performed according to previously described methods [2,5,[8][9][10]. General anesthesia with endotracheal intubation, antibiotic prophylaxis and intravenous heparin (100 IU/kg) were used in all patients.…”
Section: Methodsmentioning
confidence: 99%
“…216 Fracture rate was reduced to <5% in the postapproval study cohort in which homografts were prestented and valve-in-valve cases were included. 217 The evolution of percutaneous pulmonary valve replacement technology offers the hope for patients after Rastelli operation to have fewer reoperations.…”
Section: Assessment Of Postoperative Tga With Cardiac Catheterizationmentioning
confidence: 99%